2009
DOI: 10.1108/14777270910952261
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking impact on elderly admissions following CRHTT intervention

Abstract: Purpose -The aim of this study is to benchmark the impact of the Crisis Resolution Home Treatment Team (CRHTT) on the elderly admission rate as well as the duration of admission Design/methodology/approach -Data were collected for a period of one year before (August 2006 to July 2007) and after (August 2007 to July 2008 the extension of CRHTT input into elderly services. Findings -There was an overall reduction in the number of admissions after CRHTT got involved with the elderly. Research limitations/implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Dibben et al 5 have shown a reduction in hospital admissions and increased carer satisfaction with the introduction of CRHT teams in older people's mental healthcare. Sadiq et al 6 have also shown a reduction in admissions of elderly patients with functional disorders after the extension of CRHT teams to elderly services.…”
mentioning
confidence: 99%
“…Dibben et al 5 have shown a reduction in hospital admissions and increased carer satisfaction with the introduction of CRHT teams in older people's mental healthcare. Sadiq et al 6 have also shown a reduction in admissions of elderly patients with functional disorders after the extension of CRHT teams to elderly services.…”
mentioning
confidence: 99%